LA NOUVELLE CONFIGURATION DE L’HABITAT DANS LES QUARTIERS PRECAIRES D’ABIDJAN: CAS DE JEAN FOLLY, ZOE BRUNO ET SAGBE - Koffi, Atta; Moussa, Kone; Joseph, Kra Kouadıo (European Scientific Journal, ESJ, 2015)
The mismatch between economic growth and the demographic and spatial dynamism of the city of Abidjan is the basis of the birth in the urban landscape precarious neighborhoods. With the emergence of these districts, the state had decided initially to relocate the residents of these areas with the key operations of compensation, relocation, often poorly perceived by the population. To improve the lives of these people, at the behest of donors and with their support, the new strategy is no longer to destroy these neighborhoods, but to integrate the urban fabric by restructuring operations and equipment. This article aims to show the changes taking place in these areas at the habitat. To conduct this study we chose three shantytowns among a hundred that make up the city of Abidjan. The results of this study show an improvement in the type of housing in these neighborhoods that fit gradually into the urban fabric. This experiment is a success that avoids social conflicts between the state and the people of these often threatened with eviction neighborhoods.